Being an academic - Fanghanel, Joelle (London : Routledge, 2012)
'The role of academics in universities worldwide has undergone unprecedented change over the past decade. In this book Fanghanel discusses the effect on academics of modes of governance that have fostered the application of market principles to higher education and promoted flexibility and choice as levers for competition across the sector. She explores what it means to be an academic in the 21st century with reference to six'moments of practice' through which she analyses the main facets of academic work and the responses of academics to this neoliberal drive. Being an Academic effectively examines the frameworks that govern academic work and academic lives, and the personal beliefs and ideals that academics bring with them as educators and researchers in higher education. It argues that there is a rich, critical, empowering potential within the academy that can be harnessed to counter-balance the neoliberal stance and shape a meaningful contribution to modes of enquiry that deal with complexity and uncertainty in a global world. Drawing on empirical research collected from a global range of academics, this book examines how academics respond to structural challenges. It offers a re-appraisal of the main dynamics underpinning the professional and intellectual engagement of academics in today's universities to feed a reflection on possible responses to the complex contemporary world with which the academic endeavour is engaged. The themes explored include academics' positioning towards: - Performativity and managerialism - Regulation and professionalisation of practice - The relation to learning and students - The discipline - Research - Globalisation'-- Provided by publisher.
Includes bibliographical references (p. [120]-135) and index.
Keywords: College teaching; College teachers -- Professional relationships